To transfer or not to transfer? Evidence from validity and reliability tests for international transfers of non-market adaptation benefits in river basins. (1st January 2017) - Andreopoulos, Dimitrios; Damigos, Dimitrios
Abstract: The attempt to design cost-effective adaptation policies incorporating non-market values to inhibit climate change impacts on water resources may increase the interest in applying the Benefit Transfer method. Benefit Transfer is a practical way to consider non-market values using functions and estimates acquired through primary valuation methods from other sites. Among the primary methods, Choice Experiments appear to particularly accommodate Benefit Transfer. Nevertheless, validity and reliability of international value transfers obtained from Choice Experiments have not been adequately examined. To this end, two identical Choice Experiments were conducted in Greece and Italy in the context of river services adaptation, testing validity and reliability of Benefit Transfer. The application of validity and reliability tests for different types of transfers is supportive for the use of Benefit Transfer, at least for the value transfer types. In particular the reliability of value transfer was higher when income adjustments were taken into account. Overall, Benefit Transfer can be attentively considered to evaluate cost-effective adaptation policies across countries experiencing similar climate change trends. The latter gains more importance given that an international Benefit Transfer setting as regards the non-market benefits of adaptation to climate change for river services is absent in the relevant literature. Highlights: International transfers of river ecosystem services' non-market benefits are examined. Function and value transfers are tested for their validity and reliability. Value transfers approved valid and reliable for river adaptation to climate change. Income adjustments enhanced validity and reliability of value transfers. The inter-basin transfer of estimates for climate affected river services is genuine.